2012
DOI: 10.1021/ac3021278
|View full text |Cite
|
Sign up to set email alerts
|

2,3,4,5-Tetrakis(3′,4′-dihydroxylphenyl)thiophene: A New Matrix for the Selective Analysis of Low Molecular Weight Amines and Direct Determination of Creatinine in Urine by MALDI-TOF MS

Abstract: Small organic matrixes are still the most commonly used ones in matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) because of their advantages of high sensitivity, convenience, and cost-effectiveness. However, due to the matrix interference in the low mass region, the direct analysis of low molecular weight amines in complex surroundings with conventional organic matrixes remains a challenge. Here, a new Brønsted-Lowry acid compound 2,3,4,5-tetrakis(3',4'-dihydroxylphenyl)thiophene (DHPT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…DHB matrix peaks are indicated in red and root nodule tissue covered with DHB is shown in blue. Novel matrices such as TiO 2 nanoparticles 21 , 1,5diaminonapthalene (DAN) 22 , 2,3,4,5-Tetrakis(3′,4′-dihydroxylphenyl)thiophene (DHPT) 23 , and 1,8-bis(dimethyl-amino) naphthalene (DMAN) 24,25 have been reported that reduce the interference of matrix ions in the low mass range, and also enhance the detection of certain classes of metabolites 5 . Matrix peaks can be distinguished from real metabolites using the MS images.…”
Section: Representative Resultsmentioning
confidence: 99%
“…DHB matrix peaks are indicated in red and root nodule tissue covered with DHB is shown in blue. Novel matrices such as TiO 2 nanoparticles 21 , 1,5diaminonapthalene (DAN) 22 , 2,3,4,5-Tetrakis(3′,4′-dihydroxylphenyl)thiophene (DHPT) 23 , and 1,8-bis(dimethyl-amino) naphthalene (DMAN) 24,25 have been reported that reduce the interference of matrix ions in the low mass range, and also enhance the detection of certain classes of metabolites 5 . Matrix peaks can be distinguished from real metabolites using the MS images.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The simplest way to address the first problem is to use an alternative MALDI matrix [8][9][10], which will generate a different set of matrix cluster ions that will hopefully not mask the signal of interest. However, different MALDI matrices have different ionization/desorption characteristics and may not enable adequate ionization of the target analyte.…”
Section: Introductionmentioning
confidence: 99%
“…This showed PAI-LDI has the potential for analyzing medicine metabolism. The mass spectrum (multi-point average) of urine sample showing the entire mass range, including spiked 1-adamantylamine and urine native creatinine [35], is shown in Supplementary Figure S3. The result shows that the components of urine have little influence on analyte signal.…”
Section: Analysis Of Real Samplesmentioning
confidence: 99%